2007
DOI: 10.1111/j.1365-2044.2007.04997.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of adult intensive care in the UK

Abstract: SummaryWe wished to investigate whether intensive care represents good value for money to the National Health Service in the UK using cost-effectiveness analysis. We developed a cost-effectiveness model using secondary data sources to estimate the incremental cost per quality adjusted life year gained of treatment in intensive care vs non-intensive care treatment in adults. Estimates of hospital mortality with and without intensive care were obtained from seven published studies and from data published by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 24 publications
1
32
1
1
Order By: Relevance
“…[4][5][6][7] Aggressive ICU admission practices, however, can only be deemed inefficient to the extent that they do not improve outcomes. 8,9 Studies of patients with heterogeneous diagnoses along with studies limited to specific diseases have revealed significant hospitallevel variability in ICU use without differences in mortality. 4 Little is known, however, about how ICU use impacts outcomes other than mortality, such as cost or readmission, or how liberal ICU admission practices affect rates of invasive procedures that may contribute to downstream complications.…”
mentioning
confidence: 99%
“…[4][5][6][7] Aggressive ICU admission practices, however, can only be deemed inefficient to the extent that they do not improve outcomes. 8,9 Studies of patients with heterogeneous diagnoses along with studies limited to specific diseases have revealed significant hospitallevel variability in ICU use without differences in mortality. 4 Little is known, however, about how ICU use impacts outcomes other than mortality, such as cost or readmission, or how liberal ICU admission practices affect rates of invasive procedures that may contribute to downstream complications.…”
mentioning
confidence: 99%
“…Guidance for undertaking economic evaluations recommends that resource use should be measured beyond the short-term acute hospital setting, ideally over the time horizon of a lifetime (9,36). Recent studies have assumed that postdischarge resource use of ICU survivors is the same as that of an age-matched general population (49)(50)(51) or that of a life-expectancy-matched general population (52)(53)(54). The latter method attempts to make allowance for the higher resource consumption of ICU survivors.…”
Section: Implications For Research and Policymentioning
confidence: 98%
“…On top of the aforementioned considerations, one must take into account the following points [116]. Intensive-care treatment is cost effective in most populations including the elderly [120]. Nevertheless, older patients are at risk of poorer functional outcomes and loss of quality of life because of failure to recover preadmission living activities and acquiring additional impairments [116].…”
Section: Ethical Perspectivementioning
confidence: 99%